The Status of Geography and Environmental Studies at Secondary Level Education in Bangladesh - , Mst. Nazira Akhter Rithu; , Md. Mizanur Rahman; , Abdullah Al-Maruf (Archives of Current Research International, 2016)
The study of geography and environmental studies deals with various environmental challenges i.e. climate change, natural disasters, sea level rise, ocean environment degradation, urban pollution so on. Due to the geographical location of Bangladesh, these incidents are regular phenomena and the people of this country have to adapt these kinds of challenges. To face the onslaught of natural disasters, the knowledge of geography and environmental studies is very crucial. However, the status of this knowledge is almost obscure in the country’s education sector. Realizing the fact this present study attempted to investigate the entire condition of geography and environmental studies education and its limitation at secondary level in Bangladesh. A sample of secondary level educational institutions (n=20) under the education board of Rajshahi has been used to collect data for a period of ten months in 2012. Both primary data and secondary data have been used in the present study and the data were analyzed by various relevant statistics. The findings of the study represent that in the secondary level education the status of geography and environmental studies was not so satisfactory though the students have some basic idea about this subject. The reasons beyond the negative results are that the disinterest and discriminative approaches among the students, teachers and guardians as well as lacking of institutional facilities. At last but not the least, well planning, managements, monitoring, awareness building among the students, teachers and guardians, modifying and simplifying the teaching method can enhance the quality of geography and environmental studies education at secondary level.